Effective Leadership and Organizational Behavior in Islamic Education - Khaerunnihla Khaerunnihla; Nurul Yakin; Yudin Citriadin (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to provide an understanding of the main tasks of leadership and organizational behavior in the context of Islamic education, as well as the criteria for effective leadership and organizational behavior. The method used in this research is library research, by collecting data from various relevant sources. The results of this research conclude that understanding the main tasks and functions of leadership and organizational behavior, as well as the criteria for effective leadership and organizational behavior, is important for leaders and managers of Islamic educational institutions. This understanding helps leaders understand their duties and responsibilities in leading the organization to achieve the desired Islamic education goals. To achieve effective leadership and organizational behavior, several criteria such as a clear vision and mission, the ability to motivate and lead a team, as well as integrity and good morals are very important. Apart from that, factors such as organizational culture, leadership style, and internal and external factors also influence leadership and organizational behavior in Islamic educational institutions. Understanding and implementing these criteria can make a significant contribution to the development and improvement of the effectiveness of Islamic educational institutions.